The Pecan Bud Moth: Pest of Nursery Stock and Transplanted Pecans - Russell F. Mizell, III (EDIS)
The pecan bud moth, Gretchena bolliana (Slingerland), is a native pest of pecan and hickory throughout the pecan belt. It occurs from South Carolina to Florida and west to Texas. Arizona and New Mexico are free of this pest to date. This document is ENY-690 (formerly ENT-56), one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: December 1985. Revised: January 2004.